PENGARUH EFISIENSI, PROFITABILITAS DAN FIRM SIZE TERHADAP TAX AVOIDANCE (Studi Empiris Pada Sektor Perbankan Periode Tahun 2017 - 2021) - Yunus Nurhasan (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
This study aims to find evidence of the influence of efficiency, profitability and firm size on tax avoidance at national banks in Indonesia. The independent variables used in this research are efficiency, profitability and firm size. While the dependent variable in this study is Tax Avoidance as measured by the Effective Tax Rate (ETR). The type of research used in this research is quantitative data. The source of data used in this research is secondary data. The population in this study are national banking companies for the 5 year period 2017-2021. The determination of the research sample used a purposive sampling method and obtained a sample of 10 Banks. Testing the hypothesis in this study using multiple linear regression with the help of Eviews Version 10. The results of this study indicate that efficiency has no effect on tax evasion, profitability has a negative effect on tax evasion and firm size has an effect on tax avoidance . While simultaneously showing that the efficiency, profitability and Firm size have effect on tax avoidance